0567 DO POSITIONAL (PP) PATIENTS BECOME NON POSITIONAL PATIENTS (NPP) OVER TIME?. (28th April 2017) - Oksenberg, A; Goizman, V; Eitan, E; Nasser, K; Gadoth, N
Abstract: Introduction: Positional Obstructive Sleep Apnea (OSA) patients (PP) present breathing abnormalities only or mainly in the supine posture (supine Apnea Hypopnea Index (AHI) at least double the lateral AHI) while Non-Positional patients (NPP) have many breathing abnormalities in the lateral and supine postures. Positional Therapy (PT) i.e., the avoidance of the supine position during sleep is the obvious treatment for PP. However, if over time most of PP converts into NPP, PT is not anymore the optimal treatment. The aim of our study was to assess this topic. Methods: 81 consecutive adult PP (78% men, Age = 52.3 ± 10.3; AHI=22.9 ± 14.0, had two polysomnographic evaluations during a 6.5 years period Results: 76 patients had complete data. 52 patients (68.4%) were still PP and 24 (31.6%) became NPP. AHI LAT, weight, BMI, AHI, Max Snore Loudness Left and Right were significantly higher in NPP than PP while Min SpO2 in REM was significantly lower. 16 (66.7%) of NPP gained more ≥ 3 Kg vs.19 (36.5%) of PP (p=0.025). PP who became NPP showed a significant increase in AHI LAT vs. PP who remained PP (53.4 ± 23.3 vs. 14.1 ± 13.1, p<0.0001). Logistic Regression showed that AHI LAT was the only parameter that significantly predicts conversion from PP to NPP. For a PP each unit increase in AHI LAT augments a 13% chance to become NPP. Delta AHI LAT, OR = 1.135 (95% CI: 1.059 - 1.217, p < 0.001). Moreover, if AHI LAT increases more than 13 units, there is a 92% chance that a PP will become NPP. ROC 0.92 ± 0.04 (95% CI = 0.84 - 1.00, p<0.001). Conclusion: After 6.5 years, most PP (about 70%) are still PP. These are good news, most PP can continue to use PT to overcome their breathing abnormalities during sleep. But for about 30% of PP, PT is not anymore the optimal treatment and CPAP is probably the best alternative. AHI LAT is the most sensitive parameter that will predict if a PP will convert into NPP. The identification of PP who may become NPP over time warrants further investigation. Support (If Any):